KEHIDUPAN PEREMPUAN BANGLIAU KELURAHAN PANIPAHAN KECAMATAN PASIR LIMAU KAPAS KABUPATEN ROKAN HILIR - Desi Nila Sari; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The scriptwriter "bangliau" in the subdistrict of the cotton soils of lower rokan (the women's life study "provides an overview of the particularly lives of women making fish and wants to know the wages and adaptive strategies women use for the viability of lower rokan district. The method used in this study is a descriptive qualitative method. Where the study has found that there are several strategies that salt-making female employees use in meeting their life's needs, which are the first three strategies of active strategies, the second of passive strategies and network strategies. The women who make icana sin in the panipahan have an active strategy of doing side jobs by preparing for it at home or in storage, and so on. The passive strategy is a survival strategy employed by saltfish-making women by applying to be thrifty in the day-to-day living expenses of the family, a small income requiring the saltfish-making family to apply provident living such as reducing the child's spending on school and insufficient kitchen costs. The net strategy employed by salt-fish women in the panadea in the face of difficulty or lack of money commonly women borrow money from tauke and other relatives, where the female workers who make salty fish complain when there are difficulties such as no pawn shops for shopping or child school. Keywords: the lives of women who make salted fish, adaptive strategies in the galaxy